2002
DOI: 10.4049/jimmunol.169.9.4928
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Administration of IL-15 Augments the Antigen-Specific Primary CD8+ T Cell Response Following Vaccination with Peptide-Pulsed Dendritic Cells

Abstract: The systemic administration of IL-2 can act as a potent adjuvant for T cell-directed vaccine strategies. However, not only is the administration of IL-2 potentially toxic, but recent evidence suggests that it may also paradoxically limit the duration and magnitude of the cytotoxic T cell response. A recently identified cytokine, IL-15, shares many properties with IL-2 and may provide a preferential means of augmenting T cell-directed vaccine responses. Although well characterized in vitro, there are few data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 86 publications
5
51
0
Order By: Relevance
“…Of note, the increased numbers and percentages of donor OT-I CD8 ϩ T cells observed after cytokine treatment were sustained in the PBLs and spleen ( Figure S2) at approximately 2 months after infection in agreement other studies. 11,14,16,17,40 However, the enhanced percentage of donor OT-I CD8 ϩ T cells induced after cytokine administration did appear to wane over extended periods of time ( Figure S2E), as has also been observed with other studies. 16,17,40 We also evaluated the response of endogenous CD8 ϩ T cells in mice infected with LM-OVA using H-2K b tetramers bound with the OVA-peptide (OVAp; Figure 1D).…”
Section: Both Il-7 and Il-15 Rescue Antigen-specific Cd8 ؉ T Cells Dusupporting
confidence: 65%
See 2 more Smart Citations
“…Of note, the increased numbers and percentages of donor OT-I CD8 ϩ T cells observed after cytokine treatment were sustained in the PBLs and spleen ( Figure S2) at approximately 2 months after infection in agreement other studies. 11,14,16,17,40 However, the enhanced percentage of donor OT-I CD8 ϩ T cells induced after cytokine administration did appear to wane over extended periods of time ( Figure S2E), as has also been observed with other studies. 16,17,40 We also evaluated the response of endogenous CD8 ϩ T cells in mice infected with LM-OVA using H-2K b tetramers bound with the OVA-peptide (OVAp; Figure 1D).…”
Section: Both Il-7 and Il-15 Rescue Antigen-specific Cd8 ؉ T Cells Dusupporting
confidence: 65%
“…Both IL-7 and IL-15 increased the number of antigen-specific CD8 ϩ T cells by approximately 10-fold in the spleen by the end of treatment ( Figure 1B) in agreement with previous studies. [11][12][13][14][15][16][17][18] Interestingly, in the spleen (data not shown) and peripheral blood lymphocytes (PBLs; Figure 1C), the percentage of donor T cells was much higher with IL-15 complexes than with IL-7 complexes. This difference highlights the ability of IL-7 complexes to increase total splenocyte cell numbers without as great a proportional impact on the percentage of antigen-specific CD8 ϩ T cells, possibly the result of the distinct ability of IL-7 complexes to expand immature B-cell precursors ( Figure S1C,D).…”
Section: Both Il-7 and Il-15 Rescue Antigen-specific Cd8 ؉ T Cells Dumentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been suggested that IL-15 could favor maturation of dendritic cells, leading to augmentation of their Ag-presentation capacities (5). Finally, systemic administration of IL-15 increases the priming of Ag-specific CD8 + T cells (6). Unlike a large majority of cytokines, IL-15 can be presented by an APC that concomitantly expresses IL-15 and IL15Ra to an IL-15Rb/g-expressing cell.…”
mentioning
confidence: 99%
“…The cell pellet was resuspended in 5 ml of ACK lysing buffer, incubated for 5 min at room temperature, and then diluted with 45 ml of PBS; the cell suspension was centrifuged at 200 x g for 10 min at room temperature, and the supernatant was discarded. The cell pellet was resuspended in PBS and filtered through 45 μm cell strainer then cells were counted using a hemocytometer with trypan blue dye exclusion (Rubinstein et al, 2002).…”
Section: -Antitumor Evaluationmentioning
confidence: 99%